Use of Ethyl 2-cyanoacrylate in Skin Synthesis in Horses - Evaluation of Efficacy and Biocompatibility - de Oliveira, Gabriela Luiza; Gebara Sampaio Dória, Renata; Salles Brito, Pedro Henrique; Ricardo Ambrizi, Dewison; Morandini Reginato, Gustavo; de Assis Arantes, Julia; Alves Ferreira, Marilia; Momo, Cláudia; Domingues Lacerenza, Milena (Acta Scientiae Veterinariae, 2024)
Background: Considering the difficulties in wound healing in horses, the possibility of using a biocompatible adhesive for wound suturing presents itself as an asset for equine surgery. The tissue adhesive, which is composed of ethyl-2-cyanoacrylate, offered advantages when used in human wounds, such as the absence of discomfort, reduction of surgical and healing time, a physical barrier against environmental infectious agents, resistance to exudates, and reduction of dehiscence. The objective of this study was to evaluate the efficacy and biocompatibility of ethyl-2-cyanoacrylate as a skin adhesive in equine surgical wounds and to compare it with the use of sutures in the healing process. Materials, Methods & Results: A total of 8 horses in 2 experimental stages, neck and croup, were used and divided into 2 groups at each stage. On both sides of the neck, 7-cm-long skin incisions were made, which were sutured with nylon thread (SG; suture group; left side of neck) or glued with ethyl-2-cyanoacrylate (AG; tissue adhesive group; right side of neck). The same procedure was performed on both sides of the croup of these animals, the left side being SG and the right side, AG. Macroscopic assessments of the surgical wounds of both groups were performed on days 1 (D1), 3 (D3), 7 (D7), 10 (D10), and 12 (D12) after surgery with standardized photographs regarding spacing and position. Animals with 70% to 100% dehiscence of the wound, i.e., with a length of more than 4.9 cm, were considered as total dehiscence and excluded from the evaluations. Aspects such as touch sensitivity, tissue consistency, volume increase and temperature, healing process, and signs of biomaterial rejection were observed. On the twelfth day after surgery (D12), a fragment of healed skin was harvested for microscopic evaluation. Tissue adhesive was considered a faster and easier method compared to SG, with advantages such as barrier function against microorganisms and the fact that it does not need to be removed. However, the major disadvantage was the high rate of dehiscence. Histopathological analysis showed a greater inflammatory infiltrate at SG, suggesting a reaction to the presence of the adhesive, in addition to being a more aggressive method of synthesis. Discussion: Ethyl 2-cyanoacrylate proved to be easy and quick to apply, with the time required for synthesis being significantly shorter compared with suturing, and caused no discomfort during the transoperative period. However, it was difficult to apply in cases of heavy bleeding because the product polymerized rapidly on contact with blood, which promoted good hemostasis but led to unsatisfactory synthesis of the wound, which may have contributed to its subsequent dehiscence. There was a significant difference between the studied groups in the presence of dehiscence, as the SG had no dehiscence compared with 50% of dehiscence in the AG as a whole (n = 16), with 37.5% considered total dehiscence and 12.5% partial wound dehiscence. One possible explanation is the high tensile force in the region, possibly due to excessive movement of the wound site, combined with the wound size of 7 cm, which is probably too large for the use of tissue adhesive alone, without deep relaxing sutures. In the present study, skin samples taken on day 12 from each group were examined. The results show that there was a greater amount of inflammatory cells in the SG than in the AG. The presence of the nylon thread as a foreign body and the greater aggressiveness in performing the suture may contribute to prolonging the inflammatory phases of the tissue repair process, as was found in this group. It was also possible to observe a greater amount of tissue reaction around the area of the AG scar, i.e. perivascular and periglandular (sebaceous and sweat glands), indicating contact dermatitis due to the presence of tissue glue. Keywords: healing, horses, wounds, surgical adhesive, cyanoacrylates.